Different Soil-Structure Interaction Modelling Strategies for Seismic Analysis of a Masonry Church - Ozmen, Alper; Sayin, Erkut (Taylor & Francis Inc, 2025)
Masonry structures can be damaged different external reasons such as war, flood, earthquake etc. For protecting and transfer to the next generations, these structures can be examined detailed. Finite element analysis has generally been used for the seismic evaluation of masonry structures. The fixed base assumption has been used in traditional finite element analysis of masonry structures. Interacting with the surrounding soil and structure was generally ignored. The seismic behavior of masonry structures is significantly influenced by the soil-structure interaction (SSI). There are various soil structure interaction modelling strategies in the recent studies. In this paper, the dimensions, mechanical properties and material model of the soil are considered constant. One of them had no soil-structure interaction. The others, roller support case, fixed support case, absorbing boundary case, free field columns and Winkler supports. Variations in the seismic response of a historical masonry church were investigated using 4 different SSI models and a fixed base (SSI ignored) model. Nonlinear time history analyses were employed for the finite element analysis. The soil borehole provided the material characteristics of the surrounding soil. According to the analysis results, higher response amplitudes were obtained when SSI was considered.
Keywords: absorbing boundary; nonlinear time history analyses; seismic response; soil structure interaction; masonry church